PENERAPAN INTREPRETATIVE STRUCTURAL MODELING(ISM) DALAM PENENTUAN ELEMEN PELAKU DALAM PENGEMBANGAN KELEMBAGAAN SISTEM BAGI HASIL PETANI KOPI DAN AGROINDUSTRI KOPI - Makmur Sianipar (AGROINTEK, 2012)
Coffee farmer and agroindustry facebankcruptcy riskif they operate separately. This research aim to designa key actor in profit sharing institutional development. There are ten actor in coffee value chain resulted by Interpretative Structural Modelling (ISM)methode, consisted of facilitator, coffee agroindustry, local government, intermediary, financial institution, farmer organization, RD,central government, eksportir and coffee farmer